Observation of a Venice in Lockdown. Tourism, A Venetian Pharmakon: Unique Remedy, Addictive Poison and Easy Scapegoat - Prosper Wanner (Mondes du Tourisme, 2022)
Venice was one of the first cities in Europe to be in lockdown. The article proposes to observe this unique moment “out of tourism” from the angle of pharmacology. The concept of pharmakon is borrowed from the philosopher Bernard Stiegler as a tool for analysing tourism from its ambivalence, at once a remedy, poison and scapegoat. The in-situ observation of the one hundred days of the first lockdown relates to places, people and stories that have become visible: nature, mendicanti (beggars), pendolari (commuters) and public space. As the effects of over-tourism disappeared, this moment out of tourism made manifest the causes of Venice’s heavy dependence on tourism, until then little discussed, such as the property market, tariff discrimination and tourism intermediation. These observations offer a different perspective on an over-tourism whose mordi fuggi (those who “bite and run”) would be the main cause and which the city wishes to limit through the introduction of a city entrance tax.